The ulama, the state, and politics in Malaysia - Abdullah, Walid Jumblatt (2022)
This paper investigates the relationship between the state and Islam in Malaysia under the previous Barisan Nasional (BN) regime, focusing on the role of the ulama (Islamic religious scholars). Interactions between the ulama and the state redefine, or have the potential to do so, the contours of both the state and Islam. Drawing upon the concept of political opportunities, the paper argues that the more liberating the political opportunities are for the ulama, the more the state has to acquiesce to their demands, and thus, the ulama’s understandings of Islam. In Malaysia, wide political opportunity structures enable the ulama to drive rising conservatism, both with regard to the state and Malaysian society. The process of defining Islam is not static, as the case of Malaysia demonstrates, since the ulama adjust the definitions of Islamic concepts based on socio-political conditions. This study is situated within the literature on state-society relations, and Islam in politics.